Upper body aerobic and anaerobic capacity in canoe and kayak paddlers: Aspects of age and gender - Heller, J.; Vodicka, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Canoe and kayak flat water paddling are upper-body sports that make varying demands for upper body aerobic and anaerobic capacity. There is only little evidence on the upper body aerobic and anaerobic capacity data in paddlers across the different age categories and/or males and females using the same methods and test protocols (Bishop, 2000). Therefore, the aim of the present study was to evaluate the physiological parameters obtained in upper body aerobic and anaerobic exercise tests in young (youngster, youth junior and junior) and adult (senior) trained male and female paddlers and evaluate the results from point of view of age and gender. Methods: Altogether 306 elite flat water paddlers (99 female kayak paddlers, 135 kayak and 72 canoe male paddlers) were tested by a 30-s Wingate anaerobic arm test at a resistance load 4 W.kg-1 (=0.069 kg.kg-1) in males and 3.3 W.kg-1 (=0.057 kg.kg-1) in females, and an incremental maximum aerobic arm-cranking test. The results were compared in canoe paddlers and in male and female kayak paddlers in four age categories 13 to 14 ("youngster"), 15 to 16 ("youth junior") and 17 to 18 and years of age (junior) and in seniors (19 years and older), respectively. Statistics included correlation analysis and a 2-way ANOVA was used to determine the effects of gender and age. Results: Maximum aerobic performance in male canoe and kayak paddlers increased from 13-14 to 15-16 age category and was not different in junior (17-18 years) and senior paddlers. However, in the anaerobic arm test, both peak power and mean power output increased with age from the youngest to the oldest age categories. These anaerobic capacity indices were strongly related to the amount of fat-free mass (PP: r= 0.69 and r= 0.62; MP: r= 0.72 and r= 0.71 for the canoe and kayak paddlers, respectively). In female kayak paddlers, the indices of upper body aerobic and anaerobic capacity also increased with age, however the differences among the age groups were smaller than in male paddlers. In contrast to male paddlers, in female kayak paddlers the upper body aerobic and anaerobic capacity indices (relative to body mass) were unrelated to the amount of fat free mass. Discussion: The results of the present study seem to be comparable with the previous reported data in paddlers including gender differences in aerobic and anaerobic performances of paddlers (Bishop, 2000; Fry and Morton, 1999). It could be concluded that aerobic upper body capacity in canoe and kayak paddlers is increasing from the youngster to the junior age category. Higher upper body anaerobic capacity, lower body fat and a higher amount of fat-free mass may account for the main physiological differences between senior and junior flat water paddlers.